Crystallization of the light-harvesting chlorophyll a/b complex within thylakoid membranes (The Rockefeller University Press, 1985)
We have found that treatment of the photosynthetic membranes of green plants, or thylakoids, with the nonionic detergent Triton X-114 at a 10:1 ratio has three effects: (a) photosystem I and coupling factor are solubilized, so that the membranes retain only photosystem II (PS II) and its associated light-harvesting apparatus (LHC-II); (b) LHC-II is crystallized, and so is removed from its normal association with PS II; and (c) LHC-II crystallization causes a characteristic red shift in the 77 degrees K fluorescence from LHC-II. Treatment of thylakoids with the same detergent at a 20:1 ratio results in an equivalent loss of photosystem I and coupling factor, with LHC-II and PS II being retained by the membranes. However, no LHC-II crystals are formed, nor is there a shift in fluorescence. Thus, isolation of a membrane protein is not required for its crystallization, but the conditions of detergent treatment are critical. Membranes with crystallized LHC-II retain tetrameric particles on their surface but have no recognizable stromal fracture face. We have proposed a model to explain these results: LHC- II is normally found within the stromal half of the membrane bilayer and is reoriented during the crystallization process. This reorientation causes the specific fluorescence changes associated with crystallization. Tetrameric particles, which are not changed in any way by the crystallization process, do not consist of LHC-II complexes. PS II appears to be the only other major complex retained by these membranes, which suggests that the tetramers consist of PS II.